2003
DOI: 10.1023/a:1022683626905
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: We have previously shown that both n-3 (fish oil) and n-6 (soybean oil) PUFA-rich diets reduce carrageenan-induced paw edema in rats. The present study evaluated the role of corticosteroids, and the effect of indomethacin on this response. Basal (pre-carrageenan) levels of corticosterone were elevated in both lipid diets compared to the chow diet. During inflammation, corticosterone levels increased to a similar extent in the chow and lipid diets. With 2.0 mg/kg indomethacin, edema was reduced in the chow diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…Similar results were observed after 8 weeks of a PUFA-rich diet treatment only [20]. Additionally, the 8-week treatment with a PUFA-rich diet increased the corticosterone plasma concentrations in rats [21]. …”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Similar results were observed after 8 weeks of a PUFA-rich diet treatment only [20]. Additionally, the 8-week treatment with a PUFA-rich diet increased the corticosterone plasma concentrations in rats [21]. …”
Section: Introductionsupporting
confidence: 68%
“…Accordingly, Wohlers et al [21] showed that feeding rats for 7 weeks with a HF diet that was supplemented with soybean oil or fish oil (15% fat) resulted in increased serum corticosterone levels compared to those in rats fed a control diet (4% fat). Our animals fed with a soybean oil HF diet (15% fat) for only 3 weeks did not increase the serum levels of corticosterone compared to those of the control group.…”
Section: Discussionmentioning
confidence: 99%